2000
DOI: 10.1080/095006900750036262
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties in teaching the concepts of 'amount of substance' and 'mole'

Abstract: In this study the origin and evolution of the meanings of the concepts 'amount of substance' and 'mole' are described. Serious disagreements about these concepts amongst chemistry teachers and the recommendations of the international scientific community are identified. Attention is also drawn to the didactic implications that these epistemological difficulties may have for the teaching of chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
8

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 12 publications
0
43
0
8
Order By: Relevance
“…Teachers in Spain also exhibited confusion with the concept of the mole and its quantity amount of substance [70]. As in previous studies the mole was most frequently defined as a mass or a number of entities.…”
Section: Educational Papers Concerned About the Molementioning
confidence: 96%
See 2 more Smart Citations
“…Teachers in Spain also exhibited confusion with the concept of the mole and its quantity amount of substance [70]. As in previous studies the mole was most frequently defined as a mass or a number of entities.…”
Section: Educational Papers Concerned About the Molementioning
confidence: 96%
“…Furió et al found in a study of 87 texts used in secondary and university level in Spain published between 1976 and 1996 that the quantity "amount of substance" was not introduced explicitly in 95 % of the analyzed texts [70]. Frequently the mole concept was connected to mass, i.e.…”
Section: Educational Papers Concerned About the Molementioning
confidence: 99%
See 1 more Smart Citation
“…En este sentido hay que recordar las excelentes relaciones existentes entre este investigador y Maxwell y la importancia que tuvo este físico teórico en el desarrollo de las ideas científicas de Boltzmann. Desgraciadamente no pasó lo mismo en la comunidad científica centroeuropea de aquel tiempo. Las luchas entre el energetismo y el atomismo de la segunda mitad del siglo XIX son bien conocidas en la literatura (Boltzmann, 1986;Brock 1998;Furió et al, 2000;Moreno, 2006). La escuela energetista, representada por físicos como Duhem y por químicos como Ostwald, amigo y adversario científico de Boltzmann, pretendía desarrollar una ciencia superior, la Energética, que unificase la diversidad de ciencias particulares oponiéndose a una supuesta excesiva influencia de la Mecánica racional.…”
Section: Contribución Mecanicista De Boltzmann a La Termodinámicaunclassified
“…Les grandeurs en jeu sont donc la concentration, le volume et la quantité de matière, pour lesquelles les diffi cultés d'apprentissages ont été rapportées (Furio et al, 2000 ;Gandillet et al, 2003 ;Gandillet & Le Maréchal, 2003). En permettant de multiplier les situations de préparation de solutions, le simulateur doit participer à réduire ces diffi cultés.…”
Section: • Expériences De Laboratoireunclassified